Efficiency of the Patient Registration Process Using the E-Puskesmas Application at UPT Puskesmas Terjun in 2025 - Geovani Arta Sihite; Cosmas Samuel Daeli; Theresia Hutasoit (Benih : Journal of Midwifery, 2026)
This study aims to determine the efficiency of the patient registration process using the e-Puskesmas application at the Terjun Community Health Center (UPT). The research method used was qualitative with a descriptive approach, while data collection techniques were carried out through observation and interviews with two registration officers. The study was conducted from April to July at the Terjun Community Health Center. The results showed that the use of e-Puskesmas increased service efficiency, including faster registration times, easier data and patient history searches, and reduced queues due to the online queue feature through JKN Mobile. However, there were several obstacles such as occasional system errors and unstable networks, which affected the smoothness of the registration process. The conclusion is that e-Puskesmas has proven efficient in accelerating patient administration services, although IT infrastructure improvements are needed to overcome technical obstacles. This study recommends improving system stability and staff training to optimize the application.